CLIPPER 5.01 APPLICATIONS IN NON PERIODIC SYSTEM TEST DESTRUCTOR (NDT) AIRCRAFT FLIGHT COMPONENT PT. GARUDA INDONESIA - Nanang Gartiwa; Ir. Aqwam Rosadi K; Ir. Aqwam Rosadi K (Jurnal Sistem Informasi, 2000)
Information needs in the era of globalization is very important where the increasinglysophisticated technological progress requires us to follow our progress and know thetimes and evolving science.With existence of computerized system of periodic non destrocture test aircraftcomponents will accelerate information on non destructure akifitas test unit, whichhas worked well and the workload that will come.